Persisting in the attempt: changes and permanence in the identity and role of foundational NGOs in Peru 1990 - -2016 - Bobadilla Díaz, Percy (2016)
This research aims to show the organizational changes and forms of social intervention that have been assumed by NGOs that were founded in Peru between the 60s and 80s. Since 1990 these NGOs have undergone a series of changes, mainly these have been given in the development discourses that guide their projects, in the type of relations that they establish with key actors to execute them and in the way to finance their operation. It will be noted that in the field of international and local development the rules of the game for NGOs are modified: the central State and the business sector acquire a greater presence in the promotion of development projects; There is a greater orientation to the market and selling services based on efficient management; And there is a context of reduction of funds coming from international cooperation agencies. This will generate the emergence of strategic roles as a way to respond to these changes in the institutional environment. It will be noted that, although strategies have been modified and new approaches are used - linked to human development, gender, environment, governance, among others - the meaning of NGOs’ foundational social action remain in force: working with vulnerable and excluded populations.